Implementation of Good Governance and Clean Governance Towards an Effective and Dignity Bureaucracy - Didin Hadi Saputra; Lalu Putra Muhlis; Mikyarul Ilmy; Agus Suparno; M. Nasuhi; Mufidah Mufidah (Universitas Negeri Makassar, 2021)
Government governance that will lead to a good level must be continuously promoted and advertised. This campaign must be continuously carried out in order to create a clean and authoritative government and produce dignified officials. The implementation of good govenance is one of the best concepts of offering a system in democracy. The purpose of this research is to find out how the implementation of good services carried out by the state civil apparatus (ASN) in order to create a clean, dignified and good government. The method used in this research is a deft interview, namely in-depth research or qualitative research. Large organizations that run a bureaucratic system will usually have strict procedures, regulations and rules so that their operational processes tend to be less flexible. Today's bureaucracy is found in government organizations, hospitals, companies, schools, and the military.